Rapid Transcriptional Reprogramming Associated With Heat Stress-Induced Unfolded Protein Response in Developing Brassica napus Anthers - Lohani, Neeta; Singh, Mohan B.; Bhalla, Prem L. (Frontiers in Plant Science, 2022)
Climate change associated extreme high-temperature events are a severe threat to global crop productivity and food security. Heat stress events during the plant reproductive stage disrupt pollen development leading to failure of fertilization and seed set. At the molecular level, heat stress-induced accumulation of misfolded proteins triggers unfolded protein response (UPR) in both the endoplasmic reticulum (ER) and the cytoplasm to enhance the protein folding capacity of the cell. Here, we report transcriptional responses of Brassica napus anthers exposed to high temperature for 5, 15 and 30 mins to decipher the rapid transcriptional reprogramming associated with the unfolded protein response. Functional classification of the upregulated transcripts highlighted rapid activation of the ER-UPR signalling pathway mediated by ER membrane-anchored transcription factor within 5 mins of heat stress exposure. KEGG pathway enrichment analysis also identified "Protein processing in ER" as the most significantly enriched pathway pointing towards the activation of unfolded protein response (UPR) as an immediately responding critical pathway of heat stress response during B.napus anther development. Interestingly, ER membrane-associated transcription factor NAC089 that controls ER stress-induced programmed cell death was also among the rapid responders to heat stress exposure. Five minutes of heat stress also led to strong induction of cytosolic HSF-HSP heat response network. Our results present a perspective of the rapid and massive transcriptional reprogramming activated during heat stress in pollen development and highlight the need for similar studies exploring the nature and function of very early stress-responsive networks in plant cells.